Criteria and constraints: the Human Rights Committee’s test on limiting the freedom of religion or belief - Gunatillake, Gehan (Religion and human rights, 2020)
The Human Rights Committee—the treaty body established under the International Covenant on Civil and Political Rights—performs a vital function in supervising the Covenant’s implementation. This article presents an analytical account of the Committee’s approach to determining the permissibility of limitations on the freedom of religion or belief under the Covenant. It finds that the Committee has set out certain primary legal criteria when determining the permissibility of a limitation. The Committee has then articulated certain additional normative constraints that apply to states’ authority to limit rights—such as the requirement that the limitation be compatible with the principle of non-discrimination. Based on an analysis of the Committee’s general comments and jurisprudence, the author argues that the Committee has offered a path towards imposing on states a heavier burden to justify limitations on the freedom of religion or belief.